Analysis of Problems in Science Learning at The Elementary School - Zakirman Zakirman; Wienda Gusta; Chichi Rahayu (Jurnal Ilmiah Profesi Pendidikan, 2022)
Natural Sciences (IPA) is a science that studies nature along with its contents. IPA becomes one of the compulsory subjects in elementary school. The aim of this study was to describe problems in IPA learning at the elementary school level in terms of child development. This type of research is qualified descriptive. Data collection is carried out by methods of observation in schools and analyzing the relationship of findings with literature studies based on expert theories and previous research. The results of information analysis and research findings are strengthened by providing recommendations for solutions in problem solving, namely the design of a relevant learning model to be applied in IPA learning in elementary school. The results of this study are expected to provide contributions and be used as a reference in the development and strengthening of the quality in IPA learning at elementary schools level. To develop a learning model which can improve the quality of IPA learning, instructional design teachers/designers can pay attention to the main problems found in this study.